A 25-year experience of kidney transplantation in Thailand: Report from the Thai Transplant Registry - Kajohnsak Noppakun (2018)
© 2014 Asian Pacific Society of Nephrology. Aim To report the kidney transplant activity and survival data during the past 25 years from the Thai Transplant Registry. Methods By using the registry database that was collected and updated yearly by 26 transplant centres across the country, we have reported the donor, recipient, and transplant characteristics during the past 25 years from 1987 to 2012. The primary outcome was graft loss that was defined as return to dialysis, graft removal, retransplant, or patient death. Results 465 kidney transplants were performed in 2012, an 8.1% and 23.0% increase in living and deceased donor transplants compared to the previous year, respectively. Between 1987 and 2012 with the data of 3808 recipients, patient survival and graft survival improved significantly. Traffic accident was the most common cause of death in brain-dead donors. Additionally, the most common cause of end-stage kidney disease was glomerulonephritis. Infection has been among the most common causes of death in kidney transplant recipients. Conclusion We have reported the total number, the graft and the patient survival data of kidney transplant recipients in Thailand for the period from 1987 to 2012. Although the number of patients is much lower than that in the developed countries, the patients and the graft survival rates are comparable. Summary at a Glance This report from the Thai transplant registry summarises 25 years of data collected between 1987 and 2012. It is the largest kidney transplant registry in South-East Asia, incorporating data from 26 centres across the country with 3808 recipients included. As well as the dramatic increase in the number of kidney transplants being performed annually, the evolution of practice over this time period is also evident.